Bilateral Leydig cell tumor in stallion - Melo, C. M.; Papa, Frederico Ozanam [UNESP]; Prestes, Nereu Carlos [UNESP]; Alvarenga, Marco Antonio [UNESP]; Laufer-Amorim, R. (Elsevier B.V., 2007)
The authors report a rare case of bilateral Leydig cell tumor in a noncryptorchid stallion, describing the gross. and microscopic findings. An 8-year-old Appaloosa stallion was examined for a unilateral enlargement of the testis associated with discomfort during palpation and signs of colic. General health conditions were good. Fine-needle aspiration cytology of the testis provided the diagnosis of bilateral Leydig cell tumor. Bilateral orchiectomy was performed and the testes were submitted to histopathologic examination that confirmed the diagnosis of Leydig cell tumor.
Keywords: testis; interstitial cell tumor; stallion